Hedonisme Epikuros dalam Perspektif Etika Hindu - I Wayan Sunampan Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Man is never separated from the desires in the fulfillment of his life. The development of life also affects the form of human desire. The influence of materialism is sometimes human hedonism which is sometimes incompatible with Hindu ethics. But Epicurean Hedonism has a different view to hedonism in general. This paper aims to describe Epikuros's thoughts related to Hedonism. The pleasure-oriented attitude of hedonism is different from Epikuros hedonism that not only seeks material pleasure but also seeks spiritual pleasure. Spiritual pleasure can make man calm and wise, such situations are commonly called anarakxia. The hedonism taught by Epikuros aligns with the teachings on Hindu ethics that not only pursue earthly pleasures but are led to try to control themselves from earthly pleasures in order to achieve the happiness of life. The benefits of this paper can contribute to the understanding of the intersection between Epicurean thought and Hindu ethical views.